The evolution of parasite recognition genes in the innate immune system: purifying selection on Drosophila melanogaster peptidoglycan recognition proteins. - Jiggins, F.M.; Hurst, G.D. (Journal of Molecular Evolution, 2003)
Genes involved in the recognition of parasites by the acquired immune system are often subject to intense selection pressures. In some cases, selection to recognize a diverse range of parasites has resulted in high levels of polymorphism, while elsewhere the protein sequence has changed rapidly under directional selection. We tested whether parasite recognition genes in the innate immune system show similar patterns of evolution. We sequenced seven peptidoglycan recognition protein genes (PGRPs) from 12 lines of Drosophila melanogaster and one line of D. simulans and used a variety of tests to determine whether the observed mutations were selectively neutral. We were unable to detect either balancing or directional selection. This suggests that the molecular cues used by insects to detect parasites are highly conserved and probably under strong functional constraints which prevent their evolving to evade the host immune response. Therefore, interactions between these genes are unlikely to be the focus of host-parasite coevolution, at least in Drosophila. We also found evidence of gene conversion occurring between two genes, PGRP-SC1A and PGRP-SC1B.